2014
DOI: 10.1007/s00429-014-0724-x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo electroporation to physiologically identified deep brain regions in postnatal mammals

Abstract: Genetic manipulation is widely used to research the central nervous system (CNS). The manipulation of molecular expression in a small number of neurons permits the detailed investigation of the role of specific molecules on the function and morphology of the neurons. Electroporation is a broadly used technique for gene transfer in the CNS. However, the targeting of gene transfer using electroporation in postnatal animals was restricted to the cortex, hippocampus, or the region facing the ventricle in previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…First, we attempted RNA transfection using only pulses of electric current, without pressure injection of the RNA solution into the tissue; Protocols (Pr) 1–3 ( Table 1 ). Specifically, we tested the following parameter combinations: (a) low current intensity in long pulses, as routinely used for electroporating large molecules such as biotinylated dextrans into well-localized brain tissue domains ( Reiner et al, 2000 ; Frangeul et al, 2014 ) (Pr1); and (b) high-voltage at two different frequencies: 200Hz (Pr2) and 1 Hz (Pr3), as in DNA plasmid electroporation protocols ( Haas et al, 2001 ; Barnabé-Heider et al, 2008 ; Borrell, 2010 ; Ohmura et al, 2015 ). Despite a substantial number of trials, no labeling was observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we attempted RNA transfection using only pulses of electric current, without pressure injection of the RNA solution into the tissue; Protocols (Pr) 1–3 ( Table 1 ). Specifically, we tested the following parameter combinations: (a) low current intensity in long pulses, as routinely used for electroporating large molecules such as biotinylated dextrans into well-localized brain tissue domains ( Reiner et al, 2000 ; Frangeul et al, 2014 ) (Pr1); and (b) high-voltage at two different frequencies: 200Hz (Pr2) and 1 Hz (Pr3), as in DNA plasmid electroporation protocols ( Haas et al, 2001 ; Barnabé-Heider et al, 2008 ; Borrell, 2010 ; Ohmura et al, 2015 ). Despite a substantial number of trials, no labeling was observed.…”
Section: Resultsmentioning
confidence: 99%
“…However, most of such protocols require complex guidance setups such as two-photon microscopy ( Kitamura et al, 2008 ; Marshel et al, 2010 ; Pagès et al, 2015 ), and/or patch-clamp/yuxtacellular recording ( Rancz et al, 2011 ; Oyama et al, 2013 ). Recently, a simpler, “blind” protocol that combines pressure injection of plasmidic DNA and current pulses has been reported ( Ohmura et al, 2015 ). In the present study, we attempted direct, “blind” RNA transfection of Pal-eGFP-Sindbis testing different injection methods, solution vehicles, and electric pulse sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, we were also able to alter gene expression in post-mitotic cortical projection neurons by simple intra-parenchymal injections of very small liquid volumes, thus avoiding severe disruption of the surrounding brain tissue. Previous approaches that demonstrated electroporation of DNA into neurons were of low efficiency and highly invasive, requiring the implantation of electrodes into the brain tissue (Molotkov et al, 2010;Ohmura et al, 2015;Pages et al, 2015;Porrero et al, 2016). We provide the first non-viral method for transfecting adult neurons in different brain regions based on non-invasive surface electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…However, DNA electroporation is of limited efficiency and allows generally only the targeting of embryonic (Saito and Nakatsuji, 2001) and early postnatal neural stem cell compartments (Boutin et al, 2008(Boutin et al, , 2010. Postmitotic neurons or adult neural stem cells in the subventricular compartment are highly refractory to DNA electroporation (Barnabé-Heider et al, 2008;De la Rossa and Jabaudon, 2014), even though some invasive techniques were developed to locally electroporate adult mature neurons (Molotkov et al, 2010;Ohmura et al, 2015;Pages et al, 2015;Porrero et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This method has shown its capacity in introducing DNA plasmids or other vectors in various types of applications, ranging from cells to yeast and E-coli (such as ref. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ), from in vitro studies to in vivo tissues 11 12 13 14 15 16 17 . Because of the advantages of broad applicability, rapidity, technical simplicity and avoidance of using toxic chemicals, electroporation is becoming a promising tool in the research of gene therapy and DNA vaccination.…”
mentioning
confidence: 99%